They are: x and y and the expression can be simplified to 6xy
y = -6
(2,-2)
y=4x-6 and x=1 Just replace the x in the first equation with 1 and solve. y=4(1)-6 y= (-2)
3x+2y=6 2y=-3x+6 y=-1.5x+3
Well, isn't that just a delightful little expression you've got there! When we see 3x 2y, we simply have 3 times x plus 2 times y. It's like adding a sprinkle of joy to each term, creating a beautiful mathematical harmony. Just remember to take your time and enjoy the process of combining those terms together, creating a lovely mathematical masterpiece!
They are: x and y and the expression can be simplified to 6xy
y = -6
(3 * 3)(2 * 5) (9)(10) 90
2y-6=3x2y-3x-6=0-3x-6=-2y3/2x+3=yy-inercept= 3slope= y(2)-y(1)/x(2)-x(1)= 6-3/2-0= 3/2
(2,-2)
y=4x-6 and x=1 Just replace the x in the first equation with 1 and solve. y=4(1)-6 y= (-2)
Y = mX + 6 Y - 6 = mX (Y - 6)/X = m ==============If you had values you could get the integer that is m
y = 3, 6
x = 6 and y = -2
3x+2y=6 2y=-3x+6 y=-1.5x+3
2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9